A methods engineering study on JTA Packaging - Camacho, Rowena Grace (College of Engineering, 2000)
JTA Packaging is a company that produces different kinds of plastic products from two main raw materials, namely polypropylene and polyethylene. It markets its products locally to various retail and wholesale establishments such as Monterey Farms Corporation, San Miguel Food Corporations, Champan Garment Corporation and others. The study focused only on the products made from polypropylene due to the fact that it was in season this time of the year. It also focuses in the production of bottom seal type of plastic. The study analyzed the product based on the various processes involved in making it. The over all environment of the plant was observed in order to identify various problems that was occuring within the company. Upon gathering data, various analysis technique were applied, namely the Kepner-Tregoe Approach to Problem Solving. The study identified two main problems pervading within the plant by applying the Streamline Diagnosis Diagram and the Ishikawa Diagram Approach. These main problems are the lack of skills of workers and too much workload. Also addressed is the problem of unorganized storage. From the Kepner-Tregoe Approach, the researchers came up with a solution which is to train workers in order to improve their skills. As for too much workload, the study suggested that the company charge additional costs for the production of rush orders. A quota is also set above which the company will no longer accept rush orders. It is also strongly advised to improve the facility layout particularly the storage system.